Modification of activated carbon prepared from black liquor with the copper ion and its application to adsorption phenol - Amir Mohammadpour; Ahmad Hallajisani; Mohammad Azadfallah; Yahya Hamzeh (Journal of Chemical and Petroleum Engineering)
The growing demand for effective and environmentally friendly phenol removal methods has led to a growing interest in investigating the potential of using biomass-derived activated carbon. This research investigated the absorption process of phenol from wastewater using activated carbon adsorbents and activated carbon modified with copper in a batch system. Activated carbon was obtained from paper mill black liquor. The pore structure and morphology of unmodified and modified samples were investigated by BET and SEM. Modifying activated carbon with copper increased the specific surface area from 283.2 to 517.5 m2/g. The inhomogeneity in the modified AC absorbent surface is less compared to AC, and it also has a more regular surface in terms of particle size uniformity. The ability of prepared adsorbents to remove phenol in aqueous medium was evaluated by examining the effects of parameters such as adsorbent amount, pH, solution concentration, contact time, temperature effect. Based on the results, it was found that AC/Cu shows the highest adsorption rate after coming in contact with phenol solution with a concentration of 100 ppm for one hour at an optimal pH of 8. The adsorption of phenol by AC/Cu is consistent with the pseudo-second-order kinetic model. The absorption of phenol by the modified AC depends on the temperature and is an endothermic process. The increase in the amount of phenol removal with increasing temperature is more in AC/Cu. The study of the adsorbent saturation in the column system showed that AC/Cu is able to absorb more than 95% of the phenol solution with a concentration of 100 ppm up to a volume of 2700 mL. The findings of this study provide valuable insights into the field and pave the way for further research in the future.